Karakteristik dan Keanekaragaman Echinodermata Di Kawasan Perairan Pantai Lhok Geulumpang Aceh Jaya: Characteristics And Diversity Of Echinodermata In Lhok Geulumpang Beach Aceh Jaya - oktavia, rita; Suryanti, Suryanti (Biospecies, 2020)
In the Lhok Geulumpang beach area it has become a tourist location at some point along the coast. Study of the ecology and richness of marine species in Aceh Jaya still a little published. The objective this research was  study the composition of species, indeks diversity and distribution patterns of Echinodermata in the Lhok Geulumpang beach of Aceh Jaya. Research has been conducted in november-december 2019 in the Lhok Geulumpang beach of Aceh Jaya. The mehtod used is a combination of two transect methods i.e. the line transect and the quadrate transect. The first station is the location of the beach with sand substrate and there is no coral rock and the second location is with coral substrate and coral reef.  Species that have been found are collected for identification at the Biology Laboratory of STKIP Bina Bangsa Meulaboh. The results showed there were 3 (three) species of sea urchins belonging to 2 families and 3 orders. Three 3 spcies of sea urchin that have been found are Echinothrix diadema (Linnaeus, 1758), Echinothrix calamaris (Pallas, 1774) and  Colobocentrotus atratus (Linnaeus, 1758). From the results of the analysis found that evenness type (J ') on sandy substrate has a value of J' = 0.93165 and on rock substrate valued J '= 0.84251 indicates evenness of species classified as High. Based on the analysis of the Shannon wiener diversity index (H '). At sandy substrate station H '= 1.4994 shows that species diversity is low. Whereas at the rock substrate station, H'= 1.5096 is classified as moderate diversity. The Malgaref species richness index in the sandy substrate station DMg = 1.2427 and the rock substrate station obtained DMg = 1.0499 indicates the Malgaref species richness index is relatively low